Geographical Information System Design Web-Based Mapping of Hospitals In Padang City - Marfalino, Hari; Hadi, Aulia Fitrul; Surmayanti; Liana Gema, Rima (Riset Sinergi Indonesia (RISINDO), 2022)
Along with the rapid development of information technology, which can help the processing and reporting of data, it is very helpful for humans in completing work. Every aspect of life is attached to technology, the system does not have human activities that are separated from the role of technology. Information system is a system within an organization which is a combination of users, facilities, technology, media, procedures and controls aimed at obtaining complex information.The diverse hospitality sector with its uniqueness and supported by facilities and transportation facilities available in tourist areas can provide a very large government income. The Padang City Government has carried out promotions through mass media such as newspapers and pamphlets. However, this method is not enough to inform hospitality widely to local and foreign tourists. The tourists will have difficulty in determining the planning of the selection of lodging. Therefore, through the design and manufacture of a hospitality GIS, it is hoped that it can display an overview of the Padang City hospitality map so that it is more attractive and can be enjoyed by the wider community. Presentation of information in web form will make it easier for the public to access it.Geographic Information System (GIS) technology has developed rapidly. GIS is created using information derived from processing a number of data, namely geographic data or data relating to the position of objects on the earth's surface. GIS technology integrates database-based data processing operations that are commonly used today, such as capturing unique visualizations and the various advantages that geographic analysis can offer through map images. GIS can be presented in the form of a web-based application